Неразличение свистящих и шипящих согласныx в языке русских старообрядцев, живущих в США в штате Орегон - Касаткина Розалия Фрaнцевна; Касаткин, Леонид Леонидович (Kalbotyra, 1997)
The article deals with the fricative consonants in the speech of the Russian Old believers in the Аmerican State of Oregon, which came here from Turkey. The authors defines that in some cases the informants have only sibilants, whereas the hushing consonants were lost and describe in details the articulation and acoustic features of the sibilants.